Seasonal effects on body composition, muscle characteristics, and performance of collegiate swimmers and divers - Roelofs, E. J.; Smith-Ryan, A. E.; Trexler, E. T.; Hirsch, K. R. (Journal of Athletic Training, 2017)
Context: Previous researchers have indicated the importance of body composition and muscle quality in athletic performance. However, body composition and muscle-quality measures in swimmers and divers over a training season have yet to be evaluated.